Anti-acetylcholinesterase, anti-α-glucosidase, anti-leishmanial and anti-fungal activities of chemical constituents of Beilschmiedia species - Awang, Khalijah; Mollataghi, A.; Coudiere, E.; Hadi, A.H.A.; Mukhtar, M.R.; Litaudon, M.; Ata, A. (Elsevier, 2012)
Phytochemical investigation of Beilschmiedia alloiophylla has resulted in the isolation of one new alkaloid, 2-hydroxy-9-methoxyaporphine (1), and ten known natural products, laurotetanine (2), liriodenine (3), boldine (4), secoboldine (5), isoboldine (6), asimilobine (7), oreobeiline (8), 6-epioreobeiline (9), β-amyrone (10), and (S)-3-methoxynordomesticine (11). Chemical studies on the bark of B. kunstleri afforded compounds 2 and 4 along with one bisbenzylisoquinoline alkaloid,N-dimethylphyllocryptine (12). Structures of compounds 1-12 were elucidated on the basis of spectroscopic methods. All of these isolates were evaluated for their anti-acetylcholinesterase (AChE), anti-α-glucosidase, anti-leishmanial and anti-fungal activities. Compounds 1-12 exhibited strong to moderate bioactivities in aforementioned bioassays.